2001
DOI: 10.1016/s0886-3350(01)00748-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporary graft for closed-system cataract surgery during corneal triple procedures

Abstract: Performing phacoemulsification during a triple corneal procedure has many advantages. Operating in a closed chamber makes surgery easier and safer. In some cases, however, a dense corneal opacity may prevent closed-chamber surgery, necessitating the use of an open-sky technique. In these cases, a temporary corneal graft using a corneal button not suitable for penetrating keratoplasty is proposed to allow phacoemulsification and foldable intraocular lens implantation through a corneal tunnel. The temporary corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The single interrupted suture and double-layer continuous suture methods are commonly used in artificial cornea transplant or keratoplasty [121620]. Extrusion of the device was observed frequently in the single interrupted suture method than in the double-layer continuous suture in our pre-experimental study (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…The single interrupted suture and double-layer continuous suture methods are commonly used in artificial cornea transplant or keratoplasty [121620]. Extrusion of the device was observed frequently in the single interrupted suture method than in the double-layer continuous suture in our pre-experimental study (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…However, corneal opacities were still present after this procedure, visual acuity was less than after a PKP triple procedure, and cosmetic rehabilitation was difficult because of the dislocated pupil and remaining corneal opacity. Nardi et al12 showed that temporary corneal grafting using corneas that were unsuitable for PKP enabled CCC, PEA, and IOL implantation in a closed state, but this technique would be prohibitively expensive in most countries due to the need for an additional corneal button.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The capsulorhexis should be assisted with capsule staining with dye. 17 (6) Low vacuum and a low flow rate must be maintained. (7) Phacoemulsification must be performed using a divide-and-conquer technique.…”
Section: Discussionmentioning
confidence: 99%